Sensor data acquisition via bluetooth connectivity - Zhang, Bo (2008)
In this work, issues pertaining to the Bluetooth wireless communication for sensor data acquisition are investigated. Problems associated with Bluetooth wireless communication and sensor data acquisition, such as RS-232 protocol, Bluetooth protocol stack, Bluetooth Serial Port profile, as well as real time operating system, have been studied.